The midwife's tale - Parr, Delia (Parr, Delia. At home in Trinity, 2015)
"In 1830s small-town Pennsylvania, midwife Martha Cade's world changes when she faces tense relationships, a new doctor in town whose arrival threatens her job, a town scandal, and an unexpected romance"--